REVITALISASI PENDIDIKAN ISLAM DAN TANTANGAN GLOBAL - Muhlison Muhlison (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2014)
Education in history of  child  civilization of human being is one of most urgent life component. This Actifity has and will be non-stoped to walk from first of human being in world the bitter end  life on this earth. Even if pulled to retreat farther, we will get that education have started to proceed by Allah swt. creating first human being of Adam in heaven of where Allah have taught to him all of name which is by all unheard-of angel at all.